THE EFFECTIVENESS OF JAKARTA SMART CITY APPLICATION IN ENHANCING COMMUNITY RESILIENCE IN FACING FLOOD RISK - Linda Widiachristy; Adinda Smaradhana Rachmanto (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2021)
Jakarta is the most populated city in Indonesia with a long history of natural disasters, particularly floods. The city's geographical condition has been said as the leading cause of the recurrent floods that happen over the years. This situation has predominantly affected the people living in the flood-prone locations in several settlements along the Ciliwung riverbanks. The government has conducted various efforts to enhance the city resilience towards flood incidence, including utilizing smart city approach, such as flood monitoring applications to give a real-time information related to certain circumstances that possibly caused flooding. This effort aims to increase the community awareness toward disaster events.The aim of this paper is to analyse the effectiveness of people using the flood mitigation application as an early warning system in Jakarta. To construct this objective, questions for instance as to what extent people are familiar with the application, how much they understand its function, and whether they face any difficulties in using the application during the flood events are proposed. The quantitative approach is being used in this research to gather people's opinions towards the application, specifically JAKI. Preliminary results suggest that there are still some gaps in the implementation of technology applied with how society comprehends it, resulting in the interference with the application’s intention as an early warning system. Some important features that need to be reformed in favor of public use are the application basis, target group, data selection, and application in disaster management schemes. While the research is still on-going, an understanding that technology should be aligned with the community's ability to use it should be redefined in the implementation of smart city principles in Jakarta.